Historical Overview of the Development of Temporary Architecture for Tourist Accommodation (Prostor, 2025)
Temporary architecture for tourist accommodation has become increasingly important in sustainable tourism planning, yet it remains underexplored in academic research. This paper aims to define temporary accommodation architecture and identify its stages of development. The focus is on the progress of architectural and structural features of these units in the USA and Great Britain, which are considered pioneers in this sector. The research employs qualitative analysis of literature on temporary tourism architecture and uses comparative methods to examine the evolution over time. As a result, three development phases were identified and analysed in relation to the broader stages of tourism development. The study also highlights significant inconsistency and diversification in the classification of temporary accommodation units. The main contribution of this research is the introduction of a new typological classification system for temporary tourist accommodations, based on their architectural and structural characteristics.